E. Coli Hemolytic-Uremic Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
A retrospective analysis of 37 children with Escherichia coli 0157:H7-associated hemolytic-uremic syndrome (HUS) traced to contaminated hamburger meat is reported from the University of Washington, Children's Hospital, Seattle.